TRAUMA - Sinaga, Santa Darell Fido; Darmayuda, I Komang; Laksmi, Desak Made Suarti (UPT Pusat Penerbitan LP2MPP ISI Denpasar, 2024)
TRAUMA is a musical composition work based on the anxiety of the person closest to the composer but has an impact on the composer himself. This music composition work is made with a band format and supported by vocals and strings. The composer wants to use microphones into vocal effects, namely delay and reverb, to create an echoing sound produced from the composer's own voice that interprets the dark atmosphere experienced. TRAUMA is a musical work based on the empirical experience of the person closest to the composer. The composition of Trauma has three parts, namely: The first part that realizes the beginning of the trauma, the second part that realizes how the trauma becomes stronger until he loses his identity, and the third part that interprets how the closest person begins to slowly try to eliminate the trauma, and slowly try to find his identity again. Each section is characterized by a change of tempo. To create the composition Trauma, the composer refers to a method of creation written by SP. Gustami, namely: First, the exploration stage which includes observation, and searching for literature sources. Second, the design stage, which involves making several sketches and technical drawings. The third stage is realization, which is the forming process, followed by assessment and evaluation of the finished work.